Pengembangan Strategi Pemasaran Berbasis Komunitas bagi Pelaku Usaha Kerajinan Tangan di Desa Situ Gadung Kabupaten Tangerang - Sinta Sulistiani; Retno Wulansari; Ratih Andalusi (Jurnal PKM Manajemen Bisnis, 2026)
This community service activity was carried out to enhance the marketing capacity of handicraft entrepreneurs in Situ Gadung Village, Tangerang Regency. The background of the program arises from the limited market access and competitiveness of local handicraft products, which rely primarily on conventional sales channels. The main objective of this activity was to improve participants’ knowledge and skills in developing community-based marketing strategies that leverage collaboration and digital platforms. The activity was conducted on November 4–5, 2025, by six lecturers from Universitas Pamulang, with 19 local residents engaged in handicraft trading as participants. The methods of implementation included material presentation, practical exercises, group discussions, and question-and-answer sessions. The PKM process consisted of three stages: preparation, implementation, and reporting. The results indicated that participants gained better understanding of community-based and online marketing strategies, were able to collaboratively create promotional content, and successfully established a small online marketplace network within their community. This activity contributed to empowering local entrepreneurs by fostering participatory approaches and sustainable marketing practices.